Calcium sulfate veins characterized by ChemCam/Curiosity at Gale crater, Mars. Issue 9 (9th September 2014) - Nachon, M.; Clegg, S. M.; Mangold, N.; Schröder, S.; Kah, L. C.; Dromart, G.; Ollila, A.; Johnson, J. R.; Oehler, D. Z.; Bridges, J. C.; Le Mouélic, S.; Forni, O.; et al.
Abstract The Curiosity rover has analyzed abundant light‐toned fracture‐fill material within the Yellowknife Bay sedimentary deposits. The ChemCam instrument, coupled with Mastcam and ChemCam/Remote Micro Imager images, was able to demonstrate that these fracture fills consist of calcium sulfate veins, many of which appear to be hydrated at a level expected for gypsum and bassanite. Anhydrite is locally present and is found in a location characterized by a nodular texture. An intricate assemblage of veins crosses the sediments, which were likely formed by precipitation from fluids circulating through fractures. The presence of veins throughout the entire 5 m thick Yellowknife Bay sediments suggests that this process occurred well after sedimentation and cementation/lithification of those sediments. The sulfur‐rich fluids may have originated in previously precipitated sulfate‐rich layers, either before the deposition of the Sheepbed mudstones or from unrelated units such as the sulfates at the base of Mount Sharp. The occurrence of these veins after the episodes of deposition of fluvial sediments at the surface suggests persistent aqueous activity in relatively nonacidic conditions.